2011
DOI: 10.1523/jneurosci.2021-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Presynaptic Short-Term Plasticity and Information Processing in a Mouse Model of Fragile X Syndrome

Abstract: Fragile X syndrome (FXS) is the most common inherited form of intellectual disability and the leading genetic cause of autism. It is associated with the lack of fragile X mental retardation protein (FMRP), a regulator of protein synthesis in axons and dendrites. Studies on FXS have extensively focused on the postsynaptic changes underlying dysfunctions in long-term plasticity. In contrast, the presynaptic mechanisms of FXS have garnered relatively little attention and are poorly understood. Activity-dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
153
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(168 citation statements)
references
References 67 publications
14
153
1
Order By: Relevance
“…However, the overabundance of PSD scaffolding proteins, which can promote synaptic maturation, appears to be at odds with consistent findings of abnormally long, thin, and tortuous spine profiles in FXS (43). In addition, our results revealed up-regulation of many presynaptic proteins, adding weight to the idea that FMRP has phenotypically relevant presyntaptic functions (44). We observed increases in presynaptic vesicle components, including synapsin 1, VAMP2, SNAP25, syntaxin1, and the syntaxin regulators Stxbp 1 and 5, and Snph, which binds free syntaxin.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…However, the overabundance of PSD scaffolding proteins, which can promote synaptic maturation, appears to be at odds with consistent findings of abnormally long, thin, and tortuous spine profiles in FXS (43). In addition, our results revealed up-regulation of many presynaptic proteins, adding weight to the idea that FMRP has phenotypically relevant presyntaptic functions (44). We observed increases in presynaptic vesicle components, including synapsin 1, VAMP2, SNAP25, syntaxin1, and the syntaxin regulators Stxbp 1 and 5, and Snph, which binds free syntaxin.…”
Section: Discussionsupporting
confidence: 71%
“…Recent studies have provided genetic evidence that genes encoding presynaptic release factors, especially SNARE complexes genes, may play important roles in susceptibility of attention-deficit/ hyperactivity disorder (45,46) and autism, two frequent endophenotypes of FXS (47,48). Together, these data raise the prospect of altered active zone structure and release dynamics at cortical synapses in FXS and may help explain abnormalities in presynaptic function seen at hippocampal synapses in the Fmr1 KO (44).…”
Section: Discussionmentioning
confidence: 95%
“…However, paired-pulse facilitation and short-term synaptic plasticity were significantly lower in Fmr1 KO mice when compared to their wild-type controls (Klemmer et al, 2011). In agreement, Deng and colleagues reported that the abnormal short-term synaptic plasticity observed in the CA1 of Fmr1 KO mice is associated with accelerated vesicle recycling, larger vesicle pools, and increased cumulative calcium influx through N-type and P/Q-type voltage gated calcium channels (Deng et al, 2011).…”
Section: Changes In Short-term Plasticitymentioning
confidence: 75%
“…On the other hand, while short-term synaptic depression has been shown to be decreased in amplitude in Fmr1 KO slices (Deng et al, 2011), short-term potentiation has been found to be unaltered (Godfraind et al, 1996).…”
Section: Changes In Short-term Plasticitymentioning
confidence: 92%
“…Presynaptic abnormalities were reported at excitatory hippocampal synapses in a mouse model of Fragile X syndrome, leading to defects in short-term plasticity and information processing [34,35]. These changes were associated with exaggerated calcium influx in presynaptic neurons during highfrequency stimulation [34].…”
Section: Discussionmentioning
confidence: 99%